Alginate Profile, Antioxidant, and Antibacterial Activities of Brown Algae Sargassum cristaefolium from Pane Island, North Sumatera - Astrid Fauzia Dewinta; Ipanna Enggar Susetya; Khairunnisa Khairunnisa; Mai Suriani; Syahira Addina; Amanatul Fadhilah (Faculty of Fisheries and Marine Universitas Airlangga, 2023)
Highlight Research Alginate content produced by Sargassum cristaefolium in three different parts of the thallus has food grade quality. The alginate chemical profile of cristaefolium in three different thallus part had a significant effect. Antioxidant activity of cristaefolium extract was in the moderate category. Antibacterial activity of cristaefolium extract against aquatic pathogenic bacteria has moderate and strong effectiveness. Abstract Sargassum, an ubiquitous variant of algae in North Sumatera, has grown wildly on Pane Island with the type, namely, Sargassum cristaefolium. This study aimed to determine the characteristics of alginates, antioxidative ability, and antibacterial ability. Alginate was extracted via the acid pathway method from three different parts of the thallus and was then characterized physically and chemically. Antioxidant activity using the DPPH method and the total phenol with a gallic acid standard. Antibacterial activity using the well diffusion method. The characteristics of alginate include yields of 53.61% ± 2.21%, viscosity of 11.44 ± 1.54 cPs, whiteness index of 56.55 ± 1.71, acidity degrees of 9.83 ± 0.34, moisture content of 9.63% ± 0.53%, ash content of 23.17% ± 0.76%, Pb and Hg levels of 0.065 ± 0.01 ppm, 0.034 ± 0.003 ppm. The IC50 value of antioxidant activity being 134.408 ± 0.04 ppm, moderate category. Extract concentration of 8 mL can inhibit the E. coli and E. tarda with inhibitions of 10.60 ± 0.72, 14.03 ± 2.97 mm. Although other pathogenic bacteria can be inhibited optimally at an extract concentration of 10 mL with inhibitions of 11.03 ± 1.43, 9.07 ± 0.20, 11.20 ± 1.56, 12.80 ± 3.01 mm. Alginates isolated in S.cristaefolium from Pane Island met food grade standards except for its viscosity. S. cristaefolium from Pane Island is a moderate antioxidant. Likewise, its antibacterial ability was moderate however it was strong against aquatic gram-negative bacteria.